Analisis Strategi Manajemen Biaya Terhadap Kinerja Profitabilitas PT Garuda Indonesia Tbk Tahun 2021-2023 - Ari Haryanto; Sulistia Wati; Abdilah Abdilah (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze in depth the relationship between cost management strategies and the profitability performance of PT Garuda Indonesia Tbk during the period 2021 to 2023. This research is motivated by the prolonged crisis experienced by the global aviation industry due to the COVID-19 pandemic, which resulted in a drastic decline in revenue, cash flow, and profitability. In this context, PT Garuda Indonesia implemented several efficiency and restructuring strategies to save its financial condition. The research approach uses a descriptive quantitative method with secondary data sourced from the company's annual financial reports. The focus of cost management strategies includes reducing the aircraft fleet, renegotiating leasing and operating costs, reducing loss-making routes, restructuring debt with creditors and lessors, and strict control of operating costs and administrative expenses. Profitability performance is measured using indicators such as Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The results show that the implemented cost efficiency strategies have a positive impact on financial performance. The cost ratio decreased significantly from 195.19% in 2021 to 89.45% in 2023. Return on Assets (ROA) increased from -58.03% to 3.75%, while Net Operating Income (NPM) surged from -312.27% to 8.58%. Although ROE remains negative due to accumulated deficits from previous years, the trend is improving. 2022 marks a significant turning point, with significant debt restructuring and cost efficiency initiatives beginning to show tangible results, while 2023 marks a recovery phase with greater operational stability and increased passenger and cargo volumes. This study demonstrates that cost management strategies, when implemented consistently, in a structured manner, and based on sound analysis, can restore and improve a company's profitability during a crisis. These findings can serve as a practical reference for other airlines facing global economic uncertainty. Furthermore, this study contributes to the literature on financial management and operational strategy in the air transportation sector, particularly in the context of post-crisis recovery and efficiency optimization.